Metastatic Prostate Cancer of Hand - Akihito Nagano; Takatoshi Ohno; Koji Oshima; Daichi Ishimaru; Yutaka Nishimoto; Yoshiyuki Ohno; Akihiro Hirakawa; Tatsuhiko Miyazaki; Haruhiko Akiyama (Case Reports in Orthopedics)
Soft tissue metastases of prostate cancer to other sites are extremely rare, and, to our best knowledge, there have been no reports of metastasis to soft tissue of the hand. A 63-year-old man was diagnosed with prostatic cancer. During treatment, bone and soft tissue metastases to the right hand, appearing in the first web space, were observed. The tumor was resected, along with both the first and second metacarpal bones. The thumb was reconstructed by pollicization of the remaining index finger, enabling the patient to use the pollicized thumb for activities of daily living. This is the first case report of prostate cancer metastasizing to the soft tissue in hand. After wide resection, pollicization was able to reconstruct a functional hand and thumb.